Is prophetic discourse adequate to address global economic justice? - Naudé, Piet J. (HTS teologiese studies, 2011)
This article outlined key features of prophetic discourse and investigated whether this form of moral discourse adequately addresses issues of economic injustice. It is shown that the strength of prophetic discourse is its ability to denounce instances of injustice whilst at the same time announcing a God-willed alternative future. The ‘preferential option for the poor’ in Latin American liberation theologies is treated as a case study of the influence of prophetic discourse in contexts of perceived economic injustice. Also the core weaknesses of prophetic discourse are investigated, specifically its incomplete moral argument, weak moral analyses, silence on transition measures, and its inability to take a positive stance on reforms in the system from which itself benefits. In the final section it is concluded that prophetic discourse plays an indispensable role in addressing issues of global economic justice, but – taken by itself – it is not an adequate form of moral discourse to address concrete matters of justice.